Perception, practice and proximity. Qualifying threats as psychological torture in international law. - Cakal, Ergün (Torture Journal, 2021)
Background: Fear is a central dimension of torture and cruel, inhuman and degrading treatment (hereafter ‘other ill-treatment’), particularly as a part of verbal or non-verbal threats. Adjudicators and policy-makers have grappled, arguably at a greater depth than with other methods of psychological torture, with the circumstances in which fear-based methods amount to torture or other ill-treatment. The pursuit of non-coercive standards of police interrogation has further underscored the need to better distinguish the prohibited from the permitted. Upon this background, this article reviews the existing jurisprudential and social scientific literature in formulating a lens through which fear-inducing methods could be better functionally conceptualised. Method: This article has identified, through systematic full-text search of databases, texts with keywords ‘threat’, ‘fear’, ‘coercion’, ‘intimidation’, ‘distress’, ‘anguish’ and ‘psychological pressure’. The identified texts, limited to English-language journal articles, NGO reports, court-cases and UN documents from 1950 to date, were then selected for relevance pertaining to conceptual, evidentiary and legal critique provided therein. Discussion: Whilst it is broadly recognized that the deployment of fear to inflict violence can amount to torture, methods of threats or coercion are not adequately conceptualized particularly at the lower end, i.e. routine interrogational torture. Here, principles pertaining to the legitimate use of force and minimum level of severity are used as functional guidelines to distinguish the prohibited from the permitted. The power, practice and proximity of state authorities to harm necessarily qualify threats as real, immediate and credible and therefore torturous.